Artes visuais e educação inclusiva: uma abordagem relacional - Martins Júnior, José Getúlio (2017)
This research had the objective of reflecting and finding possibilities on how to work with images in Visual Arts Teaching (EAV) in a context of Inclusive Regular Education (ERI), in classrooms with students with and without Visual Impairment (DV). Through classroom experience, inclusive strategies were developed based on a relational approach (BOURRIAUD, 2009). The researcher joined with the Artist / Educator, configuring a work in which a/r/tography and action research are present (IRWIN, 2003). To deal with contradictions found along the way, it was taken as a theoretical contribution not only the principles involved in the complex thinking of Morin (2003), but his sensitive look at the question of the human condition. This study reflects a way forward, through the report of experience in the classroom in the Municipal School of Fundamental Education General Rodrigo Otávio (EMGRO) in the city of João Pessoa, state of Paraíba.